Transcriptomic adaptation of skeletal muscle in response to MICT and HIIT exercise modalities - Weihao Hong; Yisheng Luan; Jianrong Zheng; Yingzhe Xiong; Bing Zhang; Yixuan Ma (PLoS ONE, 2025)
Skeletal muscle exhibits remarkable plasticity in response to diverse stimuli, with exercise serving as a potent trigger. Varied exercise modalities, including moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT), induce distinct structural and functional adaptations on skeletal muscle. However, the underlying molecular mechanisms governing these adaptations remain poorly understood. In this study, we utilized RNA-seq to characterize the transcriptomic profile of murine gastrocnemius muscle following 8-week treadmill-based MICT (M group) and HIIT (H group). A total of 1052 DEGs were screened in H vs. M. Among the top 10 significant DEGs, Foxo1 and Myod1 are closely related to muscular physiology. Through KEGG pathway analysis, distinct adaptations were primarily identified in the FoxO, MAPK, and PI3K-AKT pathways. By analyzing the expression of myokines, a significantly higher Igf-1 expression level was observed in the M group compared to the H group. Therefore, IGF-1, a well-known upstream regulator of both the PI3K-AKT-FoxO and MAPK pathways, might drive distinct muscle adaptations through variations in Igf-1 expression induced by these two exercise modalities.